Health Behavior Awareness: Gambaran Perilaku Kesehatan Remaja terhadap Risiko Sindrom Metabolik - Maulidya Septiany; Bernadetta Germia Aridamayanti; Rifda Nur Achriyana Arif; Indah Dwi Astuti (Universitas Faletehan, 2025)
Metabolic syndrome among adolescents is an increasing health problem associated with unhealthy lifestyles, including low physical activity and high-fat, high-sugar diets. This study aimed to describe adolescent health behavior related to the risk of metabolic syndrome. A descriptive quantitative design with a cross-sectional approach was employed. A total of 100 late adolescents aged 17–21 years living in Banjarbaru City, South Kalimantan were selected using a convenience sampling technique through social media flyers. Data were collected using a validated and reliable Health Belief Model-based questionnaire (CVI = 0.89; α = 0.87) and analyzed descriptively using frequency and percentage. The results showed that most respondents had good health behavior perceptions, particularly in self-efficacy (74%), perceived susceptibility (69%), and cues to action (60%), while perceived severity remained low (53%). These findings indicate that adolescent health awareness is generally good; however, the perception of disease seriousness needs to be improved. Strengthening self-efficacy and enhancing understanding of metabolic syndrome risk are essential to foster healthy lifestyles among adolescent.